Odors Bias Time Perception in Visual and Auditory Modalities - Yue, Zhenzhu; Gao, Tianyu; Chen, Lihan; Wu, Jiashuang (Frontiers in Psychology, 2016)
Previous studies have shown that emotional states alter our perception of time. However, attention, which is modulated by a number of factors, such as emotional events, also influences time perception. To exclude potential attentional effects associated with emotional events, various types of odors (inducing different levels of emotional arousal) were used to explore whether olfactory events modulated time perception differently in visual and auditory modalities. Participants were shown either a visual dot or heard a continuous tone for 1000 ms or 4000 ms while they were exposed to odors of jasmine, lavender, or garlic. Participants then reproduced the temporal durations of the preceding visual or auditory stimuli by pressing the spacebar twice. Their reproduced durations were compared to those in the control condition (without odor). The results showed that participants produced significantly longer time intervals in the lavender condition than in the jasmine or garlic conditions. The overall influence of odor on time perception was equivalent for both visual and auditory modalities. The analysis of the interaction effect showed that participants produced longer durations than the actual duration in the short interval condition, but they produced shorter durations in the long interval condition. The effect sizes were larger for the auditory modality than those for the visual modality. Moreover, by comparing performance across the initial and the final blocks of the experiment, we found odor adaptation effects were mainly manifested as longer reproductions for the short time interval later in the adaptation phase, and there was a larger effect size in the auditory modality. In summary, the present results indicate that odors imposed differential impacts on reproduced time durations, and they were constrained by different sensory modalities, valence of the emotional events, and target durations. Biases in time perception could be accounted for by a framework of attentional deployment between the inducers (odors) and emotionally neutral stimuli (visual dots and sound beeps).